2017
DOI: 10.1002/etc.3742
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of immune responses and related proteins in Rhamdia quelen exposed to diclofenac

Abstract: Nonsteroidal anti-inflammatory drugs are among the most widely detected pharmaceuticals in surface water worldwide. The nonsteroidal anti-inflammatory drug diclofenac is used to treat many types of pain and inflammation. Diclofenac's potential to cause adverse effects in exposed wildlife is a growing concern. To evaluate the effects of waterborne diclofenac on the immune response in Rhamdia quelen (South American catfish), fish were exposed to 3 concentrations of diclofenac (0.2, 2.0, and 20.0 μg/L) for 14 d. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 76 publications
(158 reference statements)
0
4
0
2
Order By: Relevance
“…Rats were administered an intraperitoneal injection of either DS (0.5mg/ml) or MIL-101 (Fe)-DS (0.5mg/ml), 7 days post-SNI [40]. The dosage for each rat was determined by their body weight, with a standard of 2mg/kg [40]. The NS and Sham groups were given an equivalent dose of 0.9% saline.…”
Section: Drug Deliverymentioning
confidence: 99%
“…Rats were administered an intraperitoneal injection of either DS (0.5mg/ml) or MIL-101 (Fe)-DS (0.5mg/ml), 7 days post-SNI [40]. The dosage for each rat was determined by their body weight, with a standard of 2mg/kg [40]. The NS and Sham groups were given an equivalent dose of 0.9% saline.…”
Section: Drug Deliverymentioning
confidence: 99%
“…Diclofenac, a non-steroidal anti-inflammatory drug (sold under several brand names, including Voltaren) [106], induced changes in the proteome of plasma and kidney proteins of American catfish (Rhamdia quelen), after 14 days of treatment with three concentrations of the drug (0.2, 2.0 and 20.0 mg/L). The authors identified significant modifications in the expression of 20 proteins related to nitric oxide synthesis, leukocyte migration, the inflammatory process and the complement cascade, by a shotgun proteomic approach using LC-MS/MS.…”
Section: Tracing Exposure To Medicines and Recreational Drugs By Proteomicsmentioning
confidence: 99%
“…The specimen was found attached to a blue marlin Makaira nigricans caught by the commercial longline fishing fleet of Itajaí, Brazil, in the South Atlantic Ocean at 35º58′S and 33º59′W isobaths, in April 2015. The remora was euthanized by the excess of benzocaine (1 g/L) (Ribas et al 2017), total and furcal length measurements were taken using a tape, before fixation in 10% formalin solution and storage in 70% alcohol until anatomical evaluation.…”
Section: Acquisition Of Remora Osteochirmentioning
confidence: 99%